2020
DOI: 10.3389/fbioe.2020.00542
|View full text |Cite
|
Sign up to set email alerts
|

An Injectable Hydrogel Platform for Sustained Delivery of Anti-inflammatory Nanocarriers and Induction of Regulatory T Cells in Atherosclerosis

Abstract: Chronic unresolved vascular inflammation is a critical factor in the development of atherosclerosis. Cardiovascular immunotherapy has therefore become a recent focus for treatment, with the objective to develop approaches that can suppress excessive inflammatory responses by modulating specific immune cell populations. A benefit of such immunomodulatory strategies is that low dosage stimulation of key immune cell populations, like antigen presenting cells, can subsequently propagate strong proliferation and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…The size distribution and zeta potential of PS and BNZ-PS (1 mg/mL) were characterized by Zetasizer Nano-ZS using a 4 mW He-Ne 633 laser (Malvern Instruments). The morphology of PS and BNZ-PS was determined by cryo–transmission electron microscopy as described previously ( 55 ). In brief, 200 mesh Cu grids with a lacey carbon membrane (catalog LC200-CU-100, EMS) were glow discharged in a Pelco easiGlow glow discharger (Ted Pella Inc.) using an atmosphere plasma generated at 15 mA for 15 seconds with a pressure of 0.24 mbar.…”
Section: Methodsmentioning
confidence: 99%
“…The size distribution and zeta potential of PS and BNZ-PS (1 mg/mL) were characterized by Zetasizer Nano-ZS using a 4 mW He-Ne 633 laser (Malvern Instruments). The morphology of PS and BNZ-PS was determined by cryo–transmission electron microscopy as described previously ( 55 ). In brief, 200 mesh Cu grids with a lacey carbon membrane (catalog LC200-CU-100, EMS) were glow discharged in a Pelco easiGlow glow discharger (Ted Pella Inc.) using an atmosphere plasma generated at 15 mA for 15 seconds with a pressure of 0.24 mbar.…”
Section: Methodsmentioning
confidence: 99%
“…Selfassembled poly (ethylene glycol)-b-poly(propylene sulfide) (PEG-b-PPS) block copolymers have been used as versatile nanocarriers in a wide range of applications. [12,[17][18][19][20][21][22][23] Depending on the morphology employed, PEG-b-PPS nanocarriers can retain both hydrophobic and hydrophilic payloads, respectively, in their cores or aqueous interior compartments [20,21,[24][25][26] and are highly customizable through control of charge, size, and targeting moieties on their surfaces. [8,27] Nanomaterials provide a wide range of options for sustained drug and gene delivery, [19,22,28] and the development of SC targeted nanocarriers will thus provide versatile options for the long term delivery of glaucoma therapeutics following a single intracameral injection.…”
Section: Doi: 101002/smll202004205mentioning
confidence: 99%
“…It was demonstrated that such nanomedicine could effectively accumulate in the inflamed joints and subsequently alleviate major RA-related symptoms including synovial inflammation, bone erosion, and cartilage degradation. Analogously, Scott group explored anti-inflammatory potentials of PPS-based nanovehicles with distinct morphologies (i.e., spherical micelles; filamentous worm-like micelles, filomicelles; polymeric vesicles, polymersomes) against atherosclerosis [ 57 60 ]. Notably, morphology-dependent organ and cellular level biodistributions of nanocarriers assembled from PEG- b -PPS BCPs with identical surface chemistries were disclosed [ 57 ].…”
Section: Inflammation-responsive Ddssmentioning
confidence: 99%